Analisis Faktor-Faktor Pengukuran Kinerja Pegawai Dengan Menggunakan Pendekatan Human Resources Scorecard - Wirawan, Anshar (Universitas Sam Ratulangi, 2017)
The purpose of this research is to analyze performance measurement employees by using the method human resource scorecard the office manado land. This research used a quantitative approach. The research seen from fourth perspective can be concluded that the performance of all of the employee the land office Manado strong (good) and based on vision and mission organization.Keywords: Financial Perspective, Customer Perspective, Internal Business Process Perspective, Learning And Growth Perspective